Improvement of Anaerobic Digestion by Addition of Halloysite and Magnetite Powders - Jae Pil Heo; Ilho Bae; Juhee Shin; Myoung-Eun Lee; Younki Lee; Jin Mi Triolo; Seung Gu Shin (대한환경공학회지)
Objectives This study aimed to explore the potential of halloysite and magnetite powders to enhance anaerobic digestion efficiency and to compare their effects. Methods Anaerobic digestion experiments were conducted in a total of four consecutive batch processes using reactors with halloysite and magnetite powders added at concentrations of 1 g/L, 10 g/L, and 50 g/L, as well as a control reactor without any powder addition. Cumulative methane production was measured in each batch, and the Gompertz model was applied to calculate kinetic parameters, which were then compared with the control. Additionally, microbial community analysis was performed using 16S rRNA amplicon sequencing, and correlations between the powder concentrations, Gompertz kinetic parameters, and microbial groups were evaluated. Results and Discussion Both powders demonstrated an effect on improving methane production rates. When halloysite was added at a concentration of 50 g/L, an increase in methane production rate was observed in all batches. Compared to the control, the lag phase (λ) was reduced by up to 31.4%, and the maximum methane production rate (Rm) increased by 17.6%. While the effects of halloysite at concentrations of 1 g/L and 10 g/L were less significant compared to 50 g/L, trends of reduced lag phase and increased Rm were noted in at least two batches. For magnetite powder, the most effective concentration in the first and second batches was 1 g/L, but in the third and fourth batches, lag phase (λ) was reduced by up to 39.3%, and the maximum methane production rate (Rm) increased by 13.2% at concentrations of 10 g/L and 50 g/L. Microbial community analysis revealed an increased dominance of Geobacter and Methanosarcina associated with the DIET mechanism as the amount of magnetite increased. Conclusion This study confirms the potential of halloysite and magnetite powders to enhance methane production rates in anaerobic digestion processes. These findings suggest the feasibility of using powdered additives to improve the efficiency of anaerobic digestion, providing foundational data for future related research.